Key nutritional strategies to optimize performance in para athletes - Scaramella, J.; Kirihennedige, N.; Broad, E. M. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Para athletes are a high-risk population for inadequate dietary intake leading to insufficiencies in nutrients important to athletic performance. This is partly due to minimal support and resources, especially in sport nutrition education, combined with limited prior nutrition knowledge and risks associated with different impairment types. Inadequate energy, carbohydrate, protein, iron, and vitamin D status are of particular concern in Para athletes. Assessment of these key nutrients, along with sport nutrition education, is needed to empower Para athletes with the knowledge to understand their individual nutrition needs and maximize athletic performance.